2015
DOI: 10.5713/ajas.14.0526
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses and Lactation to Cutaneous Evaporative Heat Loss in <i>Bos indicus</i>, <i>Bos taurus</i>, and Their Crossbreds

Abstract: Cutaneous evaporative heat loss in Bos indicus and Bos taurus has been well documented. Nonetheless, how crossbreds with different fractional genetic proportions respond to such circumstances is of interest. A study to examine the physiological responses to cutaneous evaporative heat loss, also lactation period and milk yield, were conducted in Sahiwal (Bos indicus, n = 10, 444±64.8 kg, 9±2.9 years), Holstein Friesian (Bos taurus, HF100% (n = 10, 488±97.9 kg, 6±2.8 years)) and the following crossbreds: HF50% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…Cutaneous evaporation is recognized as the most important mode of heat dissipation in cattle. Thus, higher diameter, volume, perimeter and density of sweat gland in animals are considered to be good adaptive traits for hot environments (Jian et al, 2016). Smaller body size of tropical indigenous cattle breeds (as compared with English and European cattle) is recognized as being beneficial for surviving in harsh environments, due in part to the smaller animals' lower feed and water requirements ( Figure 3).…”
Section: Morphological Responsementioning
confidence: 99%
“…Cutaneous evaporation is recognized as the most important mode of heat dissipation in cattle. Thus, higher diameter, volume, perimeter and density of sweat gland in animals are considered to be good adaptive traits for hot environments (Jian et al, 2016). Smaller body size of tropical indigenous cattle breeds (as compared with English and European cattle) is recognized as being beneficial for surviving in harsh environments, due in part to the smaller animals' lower feed and water requirements ( Figure 3).…”
Section: Morphological Responsementioning
confidence: 99%
“…Although, lesser serum BHB concentrations were indicative of improved reproductive performance in beef cows (Mulliniks et al, 2013), in the present study, the greater BHB was observed in the Late group, in which P/AI was also greater. This relatively greater BHB detected in Late group can be associated with the increasing milk production in B. indicus (Oliveira et al, 2007;Jian et al, 2015) and the nadir of BCS after parturition (Diaz et al, 2017;Pfeifer et al, 2017). Bos indicus cows maintained on pastures have a reduction in BCS from parturition until about 80 days postpartum.…”
Section: Tablementioning
confidence: 99%
“…Cutaneous evaporation is recognized as the most important mode of heat dissipation in cattle (Jian et al 2016). Presence of smooth, light, short and thin hairs in cows help to enhance maximum heat dissipation during thermal stress conditions (Fanta 2017).…”
Section: Morphological Adaptation Of Cattlementioning
confidence: 99%